2015
DOI: 10.7494/geol.2015.41.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Mercury contamination of bottom sediments in water reservoirs of southern Poland

Abstract: Abstract:The aim of this study was to assess the mercury concentration in bottom sediments, collected from eight reservoirs located in south-eastern Poland. A DMA-80 Mercury Analyser was used for the analysis of the concentration of mercury in bottom sediments. Concentration of mercury in sediments was between 0.01-0.18 mg•kg −1 . The research results show that 13 samples are above the Polish Hg background level. Only 9 samples are below the background level. Generally, the sediments belonged to class I and II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This situation was probably caused by the fact that these reservoirs are located in the same river basin. Brzóza Stadnicka enclosed in the basin of Brzóza Królewska acts as an initial reservoir, capturing a portion of pollutants flowing in the Tarlak river (Koniarz et al 2015b ). Moreover, the lowest PAH concentrations in the sediments from the Narożniki and Głuchów reservoirs could be associated with a low C OM content and dominant sandy fraction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation was probably caused by the fact that these reservoirs are located in the same river basin. Brzóza Stadnicka enclosed in the basin of Brzóza Królewska acts as an initial reservoir, capturing a portion of pollutants flowing in the Tarlak river (Koniarz et al 2015b ). Moreover, the lowest PAH concentrations in the sediments from the Narożniki and Głuchów reservoirs could be associated with a low C OM content and dominant sandy fraction.…”
Section: Resultsmentioning
confidence: 99%
“…There are two water reservoirs built (cascade system) on the Tarlak stream: the Brzóza Stadnicka reservoir (which is very small and located higher) and the Brzóza Królewska reservoir (larger and located at a distance of approx. 5 km) (Koniarz et al 2015b ). The former is responsible for reduction of bottom erosion at the watercourse bed and for local water retention.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Con cen tra tions of THg in the lake sed i ments var ied be tween 0.082-2.21 mg • kg -1 with a high vari abil ity in dif fer ent parts of the lake; the great est Hg lev els were found near the Mielcuch Stream and Cybina River, which brought pol lut ants into the lake. Koniarz et al (2015) found that con cen tra tions of Hg in sed i ments were be - tween 0.01-0.18 mg • kg -1 . Hg con cen tra tions in bot tom sed iments were high est in the Rybnik, or ganic mat ter be ing pos sibly the most im por tant fac tor af fect ing Hg con cen tra tions and dif fu sion in the sed i ments in ves ti gated, while low Hg lev els were gen er ally re lated to the ab sence of anthropogenic ac tiv ities.…”
Section: Rivers and Lakesmentioning
confidence: 98%
“…Total metal concentration (Zn, Cd, Pb, Cu, Ni, Cr, Fe, Mn) in the sediments was assessed after hot digestion in a mixture of HNO 3 and HClO 3 (3:2 v/v) acids (suprapure, MERCK). Metal concentrations were analyzed using the ICP-OES method (Inductively Coupled Plasma Atomic Emission Spectroscopy) on an Optima 7300 DV (PerkinElmer) (Koniarz et al 2014, 2022, Baran et al 2016. The total content of Hg in the bottom sediments was determined using the Atomic Absorption Spectrophotometer (AAS) for mercury determination (Advanced Mercury Analyser, AMA 254).…”
Section: Physical and Chemical Analysismentioning
confidence: 99%